2016
DOI: 10.1159/000441523
|View full text |Cite
|
Sign up to set email alerts
|

EEG Brain Wave Activity at Rest and during Evoked Attention in Children with Attention-Deficit/Hyperactivity Disorder and Effects of Methylphenidate

Abstract: Objective: The aim of this study was to assess baseline EEG brain wave activity in children with attention-deficit/hyperactivity disorder (ADHD) and to examine the effects of evoked attention and methylphenidate on this activity. Method: Children with ADHD (n = 19) were tested while they were stimulant free and during a period in which they were on stimulant (methylphenidate) medication. Control subjects (n = 18) were tested once. EEG brain wave activity was tested both at baseline and during focussed attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…This review identified 65 ADHD studies with a median sample size of 76 (children) and 55.5 (adults; range 23–378). Of these, 56 studied children and adolescents (average age of 11 years; Kuperman et al, 1996; Clarke et al, 1998, 2001a,b,c,d, 2002a,b,c,d,e,f, 2003, 2006, 2007, 2008b, 2011, 2013, 2016; Bresnahan et al, 1999; Swartwood et al, 2003; Hermens et al, 2005a,b,c; Magee et al, 2005; Hobbs et al, 2007; Fonseca et al, 2008, 2013; Barry et al, 2009a,b, 2010; Sohn et al, 2010; Dupuy et al, 2011, 2013, 2014a,b; Lansbergen et al, 2011; Ogrim et al, 2012; Shi et al, 2012; Liechti et al, 2013; Buyck and Wiersema, 2014a,b, 2015; Poil et al, 2014; Tye et al, 2014; Kitsune et al, 2015; Roh et al, 2015; Kamida et al, 2016; Kim et al, 2016; Thomas and Viljoen, 2016; Giertuga et al, 2017; Jarrett et al, 2017; Markovska-Simoska and Pop-Jordanova, 2017; Park et al, 2017; Rommel et al, 2017; Shephard et al, 2018) and 14 studied adults (average age of 33 years; Bresnahan et al, 1999, 2006; Bresnahan and Barry, 2002; Hermens et al, 2004; Clarke et al, 2008a; Koehler et al, 2009; van Dongen-Boomsma et al, 2010; Woltering et al, 2012; Liechti et al, 2013; Buyck and Wiersema, 2014a; Poil et al, 2014; Rommel et al, 2016; Markovska-Simoska and Pop-Jordanova, 2017; Tombor et al, 2018). Five of these studies included both adults and children as participant groups (Bresnahan et al, 1999; Liechti et al, …”
Section: Resultsmentioning
confidence: 99%
“…This review identified 65 ADHD studies with a median sample size of 76 (children) and 55.5 (adults; range 23–378). Of these, 56 studied children and adolescents (average age of 11 years; Kuperman et al, 1996; Clarke et al, 1998, 2001a,b,c,d, 2002a,b,c,d,e,f, 2003, 2006, 2007, 2008b, 2011, 2013, 2016; Bresnahan et al, 1999; Swartwood et al, 2003; Hermens et al, 2005a,b,c; Magee et al, 2005; Hobbs et al, 2007; Fonseca et al, 2008, 2013; Barry et al, 2009a,b, 2010; Sohn et al, 2010; Dupuy et al, 2011, 2013, 2014a,b; Lansbergen et al, 2011; Ogrim et al, 2012; Shi et al, 2012; Liechti et al, 2013; Buyck and Wiersema, 2014a,b, 2015; Poil et al, 2014; Tye et al, 2014; Kitsune et al, 2015; Roh et al, 2015; Kamida et al, 2016; Kim et al, 2016; Thomas and Viljoen, 2016; Giertuga et al, 2017; Jarrett et al, 2017; Markovska-Simoska and Pop-Jordanova, 2017; Park et al, 2017; Rommel et al, 2017; Shephard et al, 2018) and 14 studied adults (average age of 33 years; Bresnahan et al, 1999, 2006; Bresnahan and Barry, 2002; Hermens et al, 2004; Clarke et al, 2008a; Koehler et al, 2009; van Dongen-Boomsma et al, 2010; Woltering et al, 2012; Liechti et al, 2013; Buyck and Wiersema, 2014a; Poil et al, 2014; Rommel et al, 2016; Markovska-Simoska and Pop-Jordanova, 2017; Tombor et al, 2018). Five of these studies included both adults and children as participant groups (Bresnahan et al, 1999; Liechti et al, …”
Section: Resultsmentioning
confidence: 99%
“…The physiological feedback instrument was a BioGraph Infiniti 8 channel produced by Canada Thought Technology. 51 , 52 …”
Section: Methodsmentioning
confidence: 99%
“…: obniżona samoocena i rezygnowanie z różnych działań, co wiąże się z brakiem rozwoju potencjalnych możliwości. Liczne badania [36][37][38][39] potwierdzają, że nieprawidłowości w relacjach i problemy w panowaniu nad sobą prowadzą często do nieprawidłowego kształtowania się osobowości, zachowań antyspołecznych, nasilonych zaburzeń lękowych, depresji, a także nadużywania substancji psychoaktywnych.…”
Section: Podsumowanie I Wnioskiunclassified